Izazovi partnerstva u ustanovama ranoga i predškolskoga odgoja i obrazovanja u vrijeme pandemije koronavirusa : Challenges of partnerships in early childhood and preschool education institutions during the COVID-19 pandemic - Jurčević-Lozančić, Anka (Array, 2021)
The current living circumstances caused by the global COVID-19 pandemic are considered to be deeply disturbing as they have resulted in significant changes in the lives of families around the globe. Special attention needs to be directed towards families with children with special educational needs. Since there are relatively few studies analysing the coherence of effective cooperation with educators during the pandemic, especially in our surroundings, this study aimed to examine whether certain sociodemographic characteristics of educators (years of work experience and professional qualifications) are related to specific aspects of the quality of partnerships and cooperation in early childhood and preschool education institutions during the pandemic. For the purpose of this study, a Questionnaire on the quality of partnerships between educators and parents during the out-of-the-ordinary life circumstances caused by the Covid-19 pandemic was developed and distributed to 313 educators. Correlation coefficients were calculated to test the relationship between the educators’ self-assessment of their partnerships and cooperation with parents and their work experience (in years), as well as their professional qualifications. Analysis of variance was used to test the differences in the assessment of some aspects of cooperation with regards to the work experience of the educators. The results show that educators assess their partnerships with parents during the pandemic as being of high quality and perceive themselves as competent in building partnerships with parents of all children, as well as in providing support to parents of children with disabilities. Educators with more years of work experience consider themselves as less competent in using digital technology and believe that they need more theoretical knowledge and practical experience in this aspect.